Chapter Monitoring of Posidonia oceanica meadows in the Sicilian coasts under the Water Framework Directive (WFD) - Sirchia, Benedetto (Proceedings e report, 2020)
The present paper aims to assess for the first time the ecological status of the Sicilian water bodies using the PREI (Posidonia oceanica Rapid Easy Index) method according to the Water Framework Directive (WFD, 2000/60/EC) requirements. The PREI is based on five metrics: shoot density, shoot leaf surface area, E/L ratio, depth of lower limit, and type of this lower limit. Monitoring of the 29 P. oceanica meadows allowed to classify the 20 WBs of Sicilian coasts in the first two levels of status: 10 as "high" and 10 as "good" with the PREI values ranged between 0,551 and 1.